Constructing Quality House To Improve Health Services – an applied research in Educational Baghdad Hospital - داود غسان قاسم; مولود سهى جمال (Journal of Economics and Administrative Sciences, 2014)
Quality function deployment tool is trying to improve health services through this study that will be applied in health sector environment , and be based on applying quality function deployment tool (QFD) TO preferable evaluation of main patients requirements in order to determine the technical requirements that need most attention across improving and developing health services . Main requirements are determined to patients lying in the hospital (under research) which is (educational Baghdad medicine city office) in Baghdad, and other technical requirements through personal inter views to patients and doctors of different specializations. In addition, checklists are prepared to evaluate the requirements availability in each hospital (under research) against other information related to other competitor hospital (private alrahebat hospital) .the study has depended on quality function deployment tool QFD as an entrance which direct hospital attention toward efficient improvement of health service. The research has com into asset of conclusions , the most important of them are the possibility of applying quality function deployment tool in meeting the patients requirements and to technical requirements availability for the hospital previously mentioned ,weakness in accrete determination of patient requirements that is due to in coincidence even it is relative between patient and hospital (under research) finally ,the steady has concluded a set of recommendations of them , they have to adopt tools contributing in improving health services like quality function deployment , also they should adopt plans for improving medical services quality presented in medicine city office hospitals to meet patients needs in away superior to that services presented by the private hospitals.